HUBUNGAN PENGETAHUAN TENTANG ULKUS DIABETIKUM DENGAN TINDAKAN PENCEGAHAN PADA PENDERITA DIABETES MELITUS - Marbun, Agnes Silvina; Aryani, Novita; Sinurat, Lasma Rina Efrina (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Diabetes Mellitus is a long-term disease characterized by abnormal blood glucose levels. DM can cause several complications, one of which is Diabetic neuropathy which contributes to the occurrence of wounds, causing dry skin, anhidrosis; which makes it easier for the skin to become damaged and wounds that are difficult to heal and can cause infections that contribute to gangrene. To overcome this problem, people with diabetes mellitus must have knowledge about diabetic wounds which include early detection and prevention of diabetic foot wounds. This type of research is analytic with a cross sectional study design with the aim of knowing the relationship between knowledge about diabetic wounds and wound prevention measures in patients with diabetes mellitus at Puskesmas Kenangan. The population in this study were all DM patients who were treated at the Puskesmas Kenangan who had not experienced gangrene complications as many as 25 people with a sample of 25 people, the sample was taken by total sampling. The results of the study. Knowledge of the majority of diabetic wounds was less as many as 15 people (60%) and the majority of wound prevention measures were bad as many as 19 people (76%). The conclusion is that there is a relationship between the knowledge of people with diabetes mellitus about diabetic wounds and wound prevention measures, indicated by the P value = 0.000 (p <0.05), meaning that there is a relationship between the respondent's knowledge and wound prevention measures. To add insight and knowledge about diabetic wounds and how to prevent injuries, it is recommended for DM patients to take part in counseling about diabetic wounds held both at the puskesmas and other health facilities. It is recommended for nurses to provide health education to DM patients in order to increase knowledge about diabetic wounds by attaching posters of wound prevention measures.